2022
DOI: 10.1038/s41598-022-05536-w
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of obesity and cardiometabolic risk factors in developing cardiovascular disease: a population-based cohort study

Abstract: This study aims to assess the effects of central and general adiposity on development of cardiovascular diseases (CVDs) mediated by cardiometabolic risk factors and to analyze their degree of dependency for mediating their effects. To this end, data from the the Tehran Lipid and Glucose Study cohort with 6280 participants were included in this study. The hazard ratios were calculated using a 2-stage regression model in the context of a survival model. Systolic blood pressure (BP), total serum cholesterol, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
27
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 53 publications
(42 reference statements)
0
27
0
1
Order By: Relevance
“…Modern lifestyle and dietary habits dictate the new challenges for endocrinology and diabetology. Sedentary behavior with overnutrition provokes the development of obesity and consequent metabolic complications such as insulin resistance, dyslipidemia, cardiovascular diseases, and type 2 diabetes mellitus (T2DM) [ 1 , 2 ]. However, some patients with obesity do not have any metabolic abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…Modern lifestyle and dietary habits dictate the new challenges for endocrinology and diabetology. Sedentary behavior with overnutrition provokes the development of obesity and consequent metabolic complications such as insulin resistance, dyslipidemia, cardiovascular diseases, and type 2 diabetes mellitus (T2DM) [ 1 , 2 ]. However, some patients with obesity do not have any metabolic abnormalities.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of MetS has markedly increased throughout the world over the past few decades 1 and afflicts anywhere from 10% to 84% of the population depending on age, gender, ethnicity, and lifestyle 2 . This complex disorder consists of a cluster of metabolic dysregulations including central obesity, atherogenic dyslipidemia, insulin resistance (IR), and hypertension, and is associated with an increased risk of multiple chronic diseases 2–5 . It has been demonstrated that people with MetS have a twofold increased risk of cardiovascular diseases (CVD), a fivefold increased risk of diabetes, and a 1.5‐fold increased risk of mortality in general compared to healthy individuals 3,6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Long-term obesity increases the risk of dyslipidemia and systemic inflammation, which could be common pathways to complications, arguably the most important of which are diabetes and vascular disease [ 7 ]. There is a link between excess abdominal fat and the risk of cardiovascular disease (CVD) and other cardiometabolic diseases [ 8 , 9 , 10 ]. Obesity and especially abdominal type of fat distribution are also associated with left ventricular dysfunction, quality of life, and a reduction in life expectancy [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%